METHOD FOR MASS CONCENTRATION DETERMINATION OF PHENOL AND PYROCATECHOL IN BLOOD USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The relevance of determining phenol and its main metabolite pyrocatech in the biological environment is related to the professional activities of workers of organic synthesis, bisphenols, dyes, varnishes, synthetic resins, plasticizers, stabilizers, pesticides and other industrial and household products. working conditions are characterized by the effect of phenol and pyrocatechin on health status.